A diketopyrrolopyrrole-based fluorescent probe for investigating mitochondrial zinc ions. (5th February 2018) - Du, Chenchen; Fu, Shibo; Ren, Xiaolei; Wang, Xiaohua; Wang, Zhong; Zhou, Juan; Wang, Hongyu
Abstract : We report a diketopyrrolopyrrole-based fluorescent probeDPP-Mito, which is low toxicity and mitochondrial-specific localization and could monitor the changes in the intracellular Zn 2+ concentrations. Abstract : We demonstrate a strategy to asymmetrically introduce a Zn 2+ chelator (MeO-DPEN) and a mitochondrial-targeting group (TPP) at the N -positions of both lactam moieties of diketopyrrolopyrrole (DPP) fluorophore. And two probesDPP-Mito andDPP-C2 were reported for the comparative studies. Both probes showed almost nonfluorescent due to the photo-induced electron transfer (PET) process from MeO-DPEN to DPP fluorophore. Upon an addition of Zn 2+, the fluorescence intensities of both probes increased approximately 77-fold. Both probes exhibited a high binding constant, pH insensitivity, and high metal ion selectivity. The HeLa cell fluorescence imaging studies demonstrated that both probes were low toxicity and could monitor the changes in the intracellular Zn 2+ concentrations. The confocal microscopic study showed thatDPP-Mito specifically localized in mitochondria, whileDPP-C2 was not organelle-specific.